2018
DOI: 10.1007/s00520-018-4433-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting lower limb muscle strength and cardiopulmonary fitness after allogeneic hematopoietic stem cell transplantation

Abstract: These findings suggest that improvements in muscle strength and cardiopulmonary fitness before HSCT are crucial for maintaining post-treatment physical function, especially in elderly individuals with acute GVHD requiring a long-term stay in a protective environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
1
17
0
7
Order By: Relevance
“…Acute GVHD after allogeneic HSCT has been reported to suppress physical function after transplantation [2,15,16]. However, there is no report that examines the influence of differences in the severity of acute GVHD on the clinical courses and physical function after transplantation in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Acute GVHD after allogeneic HSCT has been reported to suppress physical function after transplantation [2,15,16]. However, there is no report that examines the influence of differences in the severity of acute GVHD on the clinical courses and physical function after transplantation in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Another report showed that factors significantly associated with reduced leg extension strength after allo-HSCT included pre-procedure leg extension strength, grade of acute GVHD, age, and time interval between pre-and post-evaluation in 88 patients who received allo-HSCT 22 . Patient leg extension strength and peak VO 2 were significantly reduced after allo-HSCT 22 .…”
Section: Physical Function Before Allo-hsct or Hospital Admissionmentioning
confidence: 99%
“…Another report showed that factors significantly associated with reduced leg extension strength after allo-HSCT included pre-procedure leg extension strength, grade of acute GVHD, age, and time interval between pre-and post-evaluation in 88 patients who received allo-HSCT 22 . Patient leg extension strength and peak VO 2 were significantly reduced after allo-HSCT 22 . Another study showed that both allogeneic (n = 11) and autologous (n = 11) HSCT patients with lower peak VO 2 had higher symptom burdens and inferior QOL during the early post-HSCT period 23 .…”
Section: Physical Function Before Allo-hsct or Hospital Admissionmentioning
confidence: 99%
“…Advancement in allo-HSCT conditioning regimens, treatments for opportunistic infectious complications, and management of graft versus host disease (GVHD) have improved the five-year net survival rate for blood-related cancers [ 1 ]. Unfortunately, allo-HSCT patients experience significant reductions in physical capacity as a result of pre-transplant conditioning regimens [ 2 , 3 , 4 , 5 ] and post-transplant comorbidities [ 6 ] that are associated with reduced psychological wellbeing [ 7 , 8 ], survival [ 9 , 10 ], and short- and long-term health-related quality of life (HRQOL) [ 11 , 12 ]. Compounding this, physical capacity is further impacted by prolonged physical inactivity during hospital stays [ 13 ].…”
Section: Introductionmentioning
confidence: 99%